ergashev22@gmail.com THE ROLE OF COGNITIVENES IN TEACHING LANGUAGE FOR ELEMENTARY AND PRESCHOOL CHILDREN: THE ROLE OF COGNITIVENES IN TEACHING LANGUAGE FOR ELEMENTARY AND PRESCHOOL CHILDREN - Ergashev, M.Ergashev (Журнал иностранных языков и лингвистики, 2022)
Cognitive learning is presented as the main point of the educational process, which develops a set of mental abilities and various ways of learning and techniques in this article.